Implementation of Lean Construction To Reduce Project Delays - Ihsabaihaki, Ainur; Patriadi, Andi; Sajiyo, Sajiyo (Devotion : Journal of Research and Community Service, 2025)
Delays in construction projects often result in resource waste and conflicts among stakeholders. This study focuses on the application of Lean Construction within the "Improve" phase of the Lean Six Sigma framework as a solution to minimize project delays. Lean Construction techniques, particularly Value Stream Mapping (VSM), are utilized to identify and eliminate inefficiencies in the construction process. The implementation of these methods in a case study of PT Golden Union Oil's refinery project in Sidoarjo demonstrated a significant reduction in waste by 57.49%. This achievement underscores the effectiveness of Lean Construction in streamlining project activities and enhancing overall efficiency. By integrating Lean Construction principles into the DMAIC framework, this approach offers systematic and practical strategies for addressing delays in construction projects. The findings contribute to the broader understanding of how innovative management techniques can optimize project delivery timelines and resource utilization in the construction industry.